A Case of Intestinal Granular Calcifications Associated With Phosphate Binder Use in a Patient on Hemodialysis - Takaaki Nagao; Yosuke Azuma; Ryo Ichibayashi (Clinical Case Reports)
ABSTRACT An experienced physician correctly identified a high‐intensity intestinal X‐ray from Lanthanum Carbonate, preventing unnecessary tests and enabling proper treatment. Awareness of this is vital in managing renal failure patients.